2019
DOI: 10.3892/etm.2019.8382
|View full text |Cite
|
Sign up to set email alerts
|

The preventive and therapeutic application of garlic and other plant ingredients in the treatment of periodontal diseases (Review)

Abstract: Since ancient times, pharmacologically active ingredients derived from natural sources, including plants and microbials have been used in the treatment of a wide array of diseases, such as atherosclerosis, diabetes mellitus and cancers. Herbal extracts and polyphenols are produced from herbs that contain a variety of ingredients, most of which exhibit anti-inflammatory, anti-oxidative and anti-microbial actions. Gingivitis is triggered by the infection of the periodontal tissues with periodontal disease-causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Aged garlic extract prepared by ageing garlic for >10 months in ethanol found to contains pharmacologically active sulfur-containing amino acids, such as SAC, S-1-propenylcysteine (SIPC), SAMC and DAS. It was demonstrated that DAS reduces inflammatory reactions elicited by Porphyromonas gingivalis derived lipopolysaccharide (LPS) in human gingival fibroblast cells and inhibits the growth of periodontal microbials [ 83 ]. A recent in vivo study reported that GE prevents the cells from different phases of cancer by neutralizing the free radicals, increasing the actions of antioxidant enzymes such as glutathione S-transferase and catalase, avoiding chromosomal damage, DNA repair mechanisms and improving glutathione contents [ 84 ].…”
Section: Bioactivities Of Ge In Alleviating the Oral Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aged garlic extract prepared by ageing garlic for >10 months in ethanol found to contains pharmacologically active sulfur-containing amino acids, such as SAC, S-1-propenylcysteine (SIPC), SAMC and DAS. It was demonstrated that DAS reduces inflammatory reactions elicited by Porphyromonas gingivalis derived lipopolysaccharide (LPS) in human gingival fibroblast cells and inhibits the growth of periodontal microbials [ 83 ]. A recent in vivo study reported that GE prevents the cells from different phases of cancer by neutralizing the free radicals, increasing the actions of antioxidant enzymes such as glutathione S-transferase and catalase, avoiding chromosomal damage, DNA repair mechanisms and improving glutathione contents [ 84 ].…”
Section: Bioactivities Of Ge In Alleviating the Oral Pathologiesmentioning
confidence: 99%
“…In neglected conditions, chronic inflammation leads to resorption of alveolar bone, periodontitis and loss of the tooth. Prevention or removal of dental plaque requires mechanical removal or clinical treatment with antibiotics [ 83 ]. Several indices such as GI, Modified GI, Sulcus Bleeding indices, Plaque indices have been developed primarily by correlating the visual clinic symptoms with histologically determined inflammation of gingivae [ 107 ].…”
Section: Oral Pathologies and Beneficial Role Of Ge In The Alleviationmentioning
confidence: 99%
“…The MD is a vegetarian-oriented dietary pattern providing many polyphenols with well-known antibacterial activity (41)(42)(43). In this respect, some in vitro studies showed that dietary polyphenols such as theaflavins, typical of tea, markedly inhibit the proteinase activities of P. gingivalis in a dose-dependent manner (44), thus limiting the adhesion capacity of these species in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…After full-mouth disinfection, periodontal non-surgical therapy can include the use of products having anti-inflammatory effects, increasing the host's defense, analgesic effects, the acceleration of cellular regeneration, an increase in protein synthesis, and the acceleration of tissue healing or bone regeneration [9]. The main objective of non-surgical periodontal regeneration treatment involves the obtainment of a biologically active complex of natural compounds [10][11][12] aimed at assisting periodontal healing. In this context, natural biological chemical compounds are increasingly preferred as treatment alternatives.…”
Section: Introductionmentioning
confidence: 99%